H2S poisoning effect and ways to improve sulfur tolerance of nickel cermet anodes operating on carbonaceous fuels - Chen, H.; Wang, F.; Wang, W.; Chen, D.; Li, S.; Shao, Zongping (Elsevier, 2016)
For commercialization-oriented solid oxide fuel cells, the state-of-the-art nickel cermet anodes are still the preferable choice because of their several favorable features, such as high electrical conductivity, good thermo-mechano compatibility with other cell components, and favorable electrocatalytic activity for hydrogen oxidation. One big drawback of such anodes is their susceptibility to sulfur poisoning, which may cause catastrophic damage to cell performance even at ppm concentration level in fuel gas, while practical fuels usually contain a certain amount of sulfur impurity with concentration usually higher than ppm level. In an attempt to make them applicable for operation on practical carbonaceous fuels, materials/morphology/cell operation mode modification has been intensively tried to alleviate the sulfur poisoning problem. Herein, recent progress in understanding the sulfur poisoning effect on the performance of SOFCs with Ni-based cermet anodes operating on sulfur-containing methane and CO fuels, and related strategies for improving the sulfur tolerance were reviewed. The application status of SOFCs operating with sulfur-containing fuels was also referred. The purpose of this review is to provide some useful guidelines for further modifications of Ni-based cermet anodes with enhanced sulfur tolerance when operating on practical sulfur-containing carbonaceous fuels.